The Influence of Using 'CAPAT'-Based Educational Game Media on Critical Thinking Skills and Learning Interest of Students in Civic Education (PPKN) at Ar-Rohmaniyyah High School - Hosen, Hosen; Muhajir, Muhajir; Wahid, A. (ISLAMIKA, 2024)
The purpose of this study is to find out: (1) The effect of the use of educational game-based learning media "CAPAT" on students' critical thinking skills. (2) The effect of using educational game-based learning media "CAPAT" on learning interest in PPKn subjects of Arrohmaniyah High School. (3) The use of educational game-based learning media "CAPAT" for critical thinking skills and learning interest in PPKn subjects of Arrohmaniyah High School. The method уаng dіgunаkаn dаlаm реngаmbіlаn data раdа реnеlіtіаn іnі i.e. mеnggunаkаn mеtоdе "рurроѕіvе ѕаmрlіng". The results obtained showed that: (1) There was a significant influence of variable X (Use of CAPAT Educational Games) on variable Y (critical thinking skills) in class XII of SMA Arrohmaniyah Tambelangan, Sampang Regency. The value of the Correlation Coefficient is 0.566, meaning that the influence of variable X (Use of CAPAT Educational Games) on variable Y (critical thinking ability) is 56.6%. (2) There is no significant influence of variable X (Use of CAPAT Educational Games) on variable Y (Student learning interest) in class XII of SMA Arrohmaniyah Tambelangan Sampang Regency, the influence of variable X (Use of CAPAT Educational Games) on variable Y (Student learning interest) is only 0.5%. (3) The CAPAT educational game method can increase students' interest in learning and their critical thinking skills in PPKn subjects at SMA Arrohmaniyah Tambelangan Sampang